Constraint based Interesting Location and Mobile Web Service Sequence Mining in M-Commerce Environment - Mohbey,Krishna K (Universidad de Talca, 2016)
Recently, mobile web services have become a more emerging topic due to popularity of smart phones and laptops. Mobile web services are becoming popular because the growth of internet speeds. Mobile web service is not only useful for particular user, but also for business purposes. It is useful for growth of a particular business. For a particular business, it is important to have the knowledge of user’s interest. In M-commerce environment user’s interesting web service sequence mining is also an emerging topic now a day. If a business person knows the web service accessing sequence of any user, he can plan new information for that particular user. Today, user’s web service accessing sequence mining is based on type of service, visiting locations, timing and some specific constraints. The constraint may define the importance or utility of a particular web service. Here, we consider utility based constraint for particular user in M-commerce environment. We proposed an efficient approach, namely Mobile Web Service Sequence Mining to mine utility based user’s interesting web service accessing sequence. Experimental results show that the proposed approach is better than previous constraint based approaches.